НЕСТАЦІОНАРНІ ЕЛЕКТРОФІЗИЧНІ ПРОЦЕСИ В СИСТЕМАХ ЗНИЖЕННЯ ЗАЛИШКОВИХ НАПРУЖЕНЬ ЗВАРНИХ З’ЄДНАНЬ - Лобанов, Л.М.; Кондратенко, І.П.; Жильцов, А.В.; Карлов, О.М.; Пащин, М.О.; Васюк, В.В.; Ящук, В.А. (Інститут електродинаміки НАН України, Київ, 2016)
A three-dimensional integral-differential mathematical model of the process of capacity discharge to the electromagnetic system with inductance coil and electrode, connected in series, was developed. The magnetic field of the coil excites the eddy currents in the electrically-conductive plate which is mounted under the coil, generating, as a result, the electromagnetic force which presses the electrode against the surface. The optimal circuit parameters were established to generate the pressing force. An electrodynamics treatment of welded joints was carried out, the modes were determined, at which the change of tension force to compression force is achieved, the fatigue strength of welded joints under the cyclic loading was increased more than twice. References 9, figures 9.